Oxidative stress and menopause-related hot flashes may be independent events - Gloria Bonaccorsi; Arianna Romani; Eleonora Cremonini; Carlo M. Bergamini; Maria Cristina Castaldini; Enrica Fila; Stefania Hanau; Leo Massari; Carlo Cervellati (Elsevier, 2015)
Objective: At present, there is growing demand for alternative, or additional, treatments to hormone replacement therapy for menopause-related hot flashes (HF). Antioxidant supplements have been recently proposed as possible candidates for this purpose, regardless of the absence of clear evidence in support of a link between these vasomotor symptoms and oxidative stress (OxS). The aim of our study was to evaluate the association between HF and OxS serum markers in a large sample of middle-aged women. Materials and methods: We conducted a cross-sectional study on 245 perimenopausal and early postmenopausal women (age 45-60 years). The variables examined were presence of self-reported HF and levels of 8-iso-prostaglandin F2α, 8-OH-deoxy-2'-guanosine, advanced oxidation protein products, total antioxidant power, uric acid, thiols, and paroxonase-1. Results: Seventy-six women (31%) reported to suffer from HF (either medium or high intensity). None of the peripheral markers of OxS examined was found to be significantly associated with the presence of HF. Conclusion: Taken together, our data suggest that systemic OxS might not be implicated with the onset of the climacteric vasomotor symptoms that most commonly affect women experiencing perimenopause and early postmenopause.